ANALISIS MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN STARBUCKS COFFEE DI JAKARTA - Helena Intania (2021)
This research is that aims to analyze the influence variabels product, price, place, promotion,process, people, physical evidence on the purchase decision starbucks coffee ini Jakarta.The method used is quantitative with descriptive analysis techniques followed by inferential analysis techniques using SmartPLS tools. This population from consumers bought and visited starbucks in Jakarta. Method sampling using non probability sampling. Data sources obtained through the results of distributing questionnaires of 96 respondents. The tools are uses SmartPLS 3.0. The result obtained are that (1) the presence of a product has a significant effect on purchasing decisions, (2) price does not have a significant effect on purchasing decisions, (3) place has no significant effect on purchasing decisions,(4)promotion has a significant effect on purchasing decisions, (5) process has no significant effect on purchasingdecisions, (6) people have a significant effect on purchasing decisions, (7) physical evidence has no significant effect on purchasing decisions. Research limitations are due to a pandemic,the spread using the G-form so there is less approach to respondents. Keywords: Marketing Mix, SmartPLS3.0, Purchasing decisions.